PENGATURAN HAK KEBEBASAN BERKEYAKINAN PENGHAYAT KEPERCAYAAN TERHADAP TUHAN YANG MAHA ESA DALAM PERSPEKTIF NEGARA HUKUM DEMOKRATIS INDONESIA - Tuti Widyaningrum (Fakultas Hukum, 2018)
ABSTRACT Article Number 28E point (1) and point (2) of UUD 1945 mentioned human rights enactment that show freedom for Indonesian citizen to choose their religion and belief, hold conscience and manifestating their ritual and consciences.That Article is the guarantee of human rights and rights of citizen of Indonesia in the the right of conscience with the Almighty God.The article 28E poin (2) UUD 1945 is closely related with article 29 poin (2) UUD 1945 that mentioned the state guarantee the freedom of religion and believ and to worship according to their religion and conscience. With the contitutional guarantee, the right of religious freedom of the religious people can enjoyed the derivation of that rights in forum internum also forum eksternum. But not so with the believers, they still have neglect of citizen rights because different faith to interpreting Belief in the one and only God. This research will analyze, 1).How the regulation of the rights of conscience believers of God in Indonesian democratic state law perspective 2) How implementation of the rights of conscience believers of God in Indonesian democratic state law perspective 3) How to make ideal regulation to regulate the rights of conscience believers of God in Indonesian democratic state law perspective. The research method is yuridis normatif. The result of this research is first, there is no regulation about protection of the rights of regious freedom of believers, and existing law just fulfill practical needs without strategical action to protect the rights of religious freedom that can setled down equaly between believers and religious people before the law and governance. The conclusion is the emptyness of law in regulating among believers can only has solution with law making that gives special protection of the rights of religious freedom of believers. The suggestion to legislative is very importance to making regulation that ruled of the rights of religious freedom believers that can give them the advantage og democratic contitutional state for fulfilling rights of citizen as same as religious people. Key words : Rights of Conscience, Citizen Rights, Believers of God